The Consept of the Capital Market According To Conventional and Islamic Perspevtives - Izazi, Muhamad Izazi Nurjaman (Journal of Economicate Studies, 2022)
This research discusses the concept of capital market in conventional and sharia glasses. Using qualitative research methods that are theoretical narratives, this study found the fact that the concepts of conventional capital markets and sharia capital markets have significant similarities and differences. The similarity can be seen from the regulations that become the legal umbrella of the implementation of its operations. The difference is can be seen from the stock index, the instrument of its products and the mechanism of its activities. Similarities and differences in capital market concepts, can provide an overview of the limitations and conditions carried out by investors. So that investors can consider investment activities that not only provide profit but the level of business achievement that is blessing in achieving benefits and fairness in order to carry out investments in accordance with the criteria of sharia principles.